Performance Comparison of Single and Double Layer Microchannel Using Liquid Metal Coolants: A Numerical Study - Sharma, Deewakar; Garg, Harry; Bajpai, P. P. (Asian Review of Mechanical Engineering, 2012)
With increase in demand for new cooling solutions, double layer configuration of microchannels has been extensively studied. Recently liquid metals have also been proposed to further improve cooling owing to their high thermal conductivity. However, their advantages with double layer system are yet to be explored. A comparative study is made between single and double layer microchannel using liquid metals (liquid gallium) as the cooling medium. The type of configuration (counter or parallel) best suited is analysed and the results are compared with single layer for four different lengths. The cross-sectional area of single layer is such that it has same flow area as that of double layer microchannel. The performance of both is compared under the conditions of same flow rate and pump power. It is judged on the basis of maximum temperature attained and minimal temperature variations at the heated surface. It is observed that with liquid metal (gallium) as coolants, the double layer arrangement doesn’t prove much advantageous and better results can be obtained using single layer. Results also favour liquid metals for small lengths of microchannels showing their favourability for miniaturized cooling systems.